Pengaruh Kinerja Keuangan terhadap Tax avoidance dengan Earning management sebagai Intervening - Tetty sulestiyo Rini; Indira Januarti (Owner : Riset dan Jurnal Akuntansi, 2025)
This study investigates how tax avoidance is affected by Return on Assets (ROA) and the Debt-to-Equity Ratio (DER), with earnings management as an intermediary variable. The research aims to identify the influence of profitability and leverage on tax avoidance decisions within Indonesia's mining industry. The study was conducted using quantitative methods at mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. Secondary data were collected from financial statements, and purposive sampling was used to select 19 companies. Data analysis included multiple regression and path analysis using Sobel tests to examine mediation effects. The results revealed that ROA positively and significantly impacts tax avoidance, while DER negatively and significantly influences it. Earnings management was found to mediate the relationships between ROA, DER, and tax avoidance significantly. These findings contribute to understanding the role of profitability, capital structure, and earnings strategies in shaping tax avoidance practices, providing valuable insights for policy and regulation formulation.